An Optofluidic Temperature Probe - Aldo Jesorka; Gavin David Michael Jeffries; Alar Ainla; Ilona Węgrzyn (Sensors, 2013)
We report the application of a microfluidic device for semi-contact temperature measurement in picoliter volumes of aqueous media. Our device, a freely positionable multifunctional pipette, operates by a hydrodynamic confinement principle, i.e., by creating a virtual flow cell of micrometer dimensions within a greater aqueous volume. We utilized two fluorescent rhodamines, which exhibit different fluorescent responses with temperature, and made ratiometric intensity measurements. The temperature dependence of the intensity ratio was calibrated and used in a model study of the thermal activation of TRPV1 ion channels expressed in Chinese hamster ovary cells. Our approach represents a practical and robust solution to the specific problem of measuring temperature in biological experiments in vitro, involving highly localized heat generation, for example with an IR-B laser.